Repeated exposure to vegetable-enriched snack bars may increase children's liking for the bars - but not for the vegetables. (1st September 2019) - Jønsson, Sofie Rye; Angka, Stephanie; Olsen, Karsten; Tolver, Anders; Olsen, Annemarie
Abstract: Most children do not consume enough vegetables and a key reason is their relatively low hedonic acceptance. The aims of this study were to test if integration of vegetables into a popular snack product might serve as a means to increase the liking for vegetables and to test how exposure frequency influences the intake and liking. Totally 256 children from 12 school classes, aged 7–10 years, participated in the study. School classes were assigned to one of six intervention groups based on the bar they were exposed to: beetroot/carrot (B/C), n = 45; spinach/Jerusalem artichoke (S/J), n = 34; pumpkin/sweet potato (P/S), n = 44; Neutral, n = 46, who received a neutral bar without vegetables; and a Boredom Group, who received the beetroot/carrot (b/c) bar at high frequency, n = 47. These groups received 8 exposures. The Boredom Group was exposed daily while the other groups were exposed every second day. A Control Group (n = 40) was not exposed. Liking for the bars was assessed at baseline and post-intervention and the intake of the bars was recorded during all exposures. Results showed increases in liking for the exposed bars in all groups except the Boredom Group, but changes were only significant in the B/C Group (p = 0.03) and the P/S Group (p = 0.02). Some increases towards unexposed bars were observed. Liking for vegetables remained stable or decreased. Intake of the bars during exposures did not differ significantly between groups, but was somewhat lower in the Boredom Group. In conclusion, repeated exposure may be a successful approach to increase liking for a vegetable bar, but does not generalize to changes in vegetable liking, and a lower exposure frequency may be advantageous.